American palm ethnomedicine: A meta-analysis - Sosnowska, Joanna (BioMed Central, 2009)
BACKGROUND: Many recent papers have documented the phytochemical and pharmacological bases for the use of palms (Arecaceae) in ethnomedicine. Early publications were based almost entirely on interviews that solicited local knowledge. More recently, ethnobotanically guided searches for new medicinal plants have proven more successful than random sampling for identifying plants that contain biodynamic ingredients. However, limited laboratory time and the high cost of clinical trials make it difficult to test all potential medicinal plants in the search for new drug candidates. The purpose of this study was to summarize and analyze previous studies on the medicinal uses of American palms in order to narrow down the search for new palm-derived medicines. METHODS: Relevant literature was surveyed and data was extracted and organized into medicinal use categories. We focused on more recent literature than that considered in a review published 25 years ago. We included phytochemical and pharmacological research that explored the importance of American palms in ethnomedicine. RESULTS: Of 730 species of American palms, we found evidence that 106 species had known medicinal uses, ranging from treatments for diabetes and leishmaniasis to prostatic hyperplasia. Thus, the number of American palm species with known uses had increased from 48 to 106 over the last quarter of a century. Furthermore, the pharmacological bases for many of the effects are now understood. CONCLUSIONS: Palms are important in American ethnomedicine. Some, like Serenoa repens and Roystonea regia, are the sources of drugs that have been approved for medicinal uses. In contrast, recent ethnopharmacological studies suggested that many of the reported uses of several other palms do not appear to have a strong physiological basis. This study has provided a useful assessment of the ethnobotanical and pharmacological data available on palms.